The Biomechanical Consequences of Arthroscopic Hip Capsulotomy and Repair in Positions at Risk for Dislocation. Issue 1 (31st December 2021) - Wach, Amanda; Mlynarek, Ryan; Maher, Suzanne A.; Kelly, Bryan T.; Ranawat, Anil
Background: The effect of interportal (IP) capsulotomy, short T-capsulotomy, and long T-capsulotomy, and their repairs, on resistance to anterior and posterior "at risk for dislocation" positions has not been quantified. Hypotheses: Our primary hypothesis was that an IP capsulotomy would have a minimal effect on hip resistive torque compared with both short and long T-capsulotomies in the at-risk dislocation positions. Our secondary hypothesis was that capsule repair would significantly increase hip resistive torque for all capsulotomies. Study Design: Controlled laboratory study. Methods: We mounted 10 cadaveric hips on a biaxial test frame in an anterior dislocation high-risk position (20° of hip extension and external rotation) and posterior dislocation high-risk position (90° of hip flexion and internal rotation). An axial force of 100 N was applied to the intact hip while the femur was internally or externally rotated at 15° per second to a torque of 5 N·m. The rotatory position at 5 N·m was recorded and set as a target for each subsequent condition. Hips were then sequentially tested with IP, short T-, and long T-capsulotomies and with corresponding repairs randomized within each condition. Peak resistive torques were compared using generalized estimating equation modeling and post hoc Bonferroni-adjusted tests. Results: For the anterior position, the IP and long T-capsulotomies demonstrated significantly lower resistive torques compared with intact. For the posterior position, both the short and long T-capsulotomies resulted in significantly lower resistive torques compared with intact. Repairs for all 3 capsulotomy types were not significantly different from the intact condition at anterior and posterior positions. Conclusion: An IP incision resulted in a decrease in capsular resistive torque in the anterior but not the posterior at-risk dislocation position, in which direction only T-capsulotomies led to a significant decrease. All capsulotomy repair conditions resulted in hip resistive torques that were similar to the intact hip in both dislocation positions. Clinical Relevance: Our results suggest that it is biomechanically advantageous to repair IP, short T-, and long T-capsulotomies, particularly for at-risk anterior dislocation positions.